Implications of Preterm Birth for Maternal Mental Health and Infant Development. Issue 2 (March 2017) - Anderson, Cheryl; Cacola, Priscila
Abstract : Abstract: Preterm birth remains a major contributor to infant mortality and morbidity including neurodevelopmental delay and childhood disability. Mothers experiencing a preterm birth are at risk for maternal mental health issues, inclusive of depression and posttraumatic stress disorder (PTSD), which may affect mother–infant attachment and infant development. Depression and PTSD, frequently comorbid, following preterm birth and relationships between these symptoms, maternal–infant attachment, and infant development are reviewed. Assessments and interventions potentially capable of benefitting mother and infant are noted. The need for healthcare professionals to intervene prenatally and at postpartum is significant as maternal distress remains one of the most consistent factors related to infant development. Although depression has received much attention in the literature as a risk factor for preterm birth, impaired attachment, and delayed infant development, some of the consequences of PTSD have only recently gained research attention. A few studies support the role of PTSD in impaired maternal–infant attachment; yet, it is unclear whether preterm infants of mothers experiencing symptoms of PTSD following birth are at a higher risk for motor development problems. Because early mother–infant interactions are influenced by prematurity as well as maternal mental health, consideration for home interventions that stimulate infant development and encourage mother–infant relationships concurrently are important. Directed interventions may be beneficial for infant development and aid in strengthening the mother–infant relationship, potentially reducing depression and PTSD symptoms in the mother. Abstract : Preterm birth can be a traumatic event as it is many times unexpected and often leads to admission to the neonatal intensive care unit (NICU). Mothers of infants in the NICU experience stress that can progress to depressive symptoms and posttraumatic stress disorder. These mental health issues can have a negative impact on maternal-infant attachment and infant development.